Peningkatkan Hasil Belajar Siswa Dan Keaktifan Siswa Menggunakan Model Problem Based Learning (PBL) Pada Mata Pelajaran PKn Kelas IV UPT SPF SD Inpres Bontomanai - Raudah Nailati; Abdul Azis; Musdalifah Syahrir (LPPM Politeknik Pratama, 2024)
The research approach used is Classroom Action Research which is carried out in 2 cycles, where each cycle consists of 4 meetings. The learning steps given in the classroom action research approach are paying attention to the teacher's explanation, asking questions during discussions, working with groups, presenting results and conclude the material. The results of the research show that there has been an increase in student learning outcomes seen from the increase in test results obtained by students in each cycle, in addition to that, student activity in class has also increased. This can be seen from the number of percentages in cycle I, the first meeting only got a percentage of 57.6% and 84.61% in the second meeting in cycle II, previously this was because students did not understand the Problem Based Learning (PBL) learning model. It was concluded that by using the Problem Based Learning (PBL) model. In class IV Civics learning at UPT SPF SD Inpres Bontomanai it is able to improve student learning outcomes and student activity